56.9k views
1 vote
What is the value of the expression f(-3) + 2f(-1) - f (4)

PLEASE HELP NO LINKS

What is the value of the expression f(-3) + 2f(-1) - f (4) PLEASE HELP NO LINKS-example-1

1 Answer

5 votes

Answer:

22

Explanation:

Find f(-3) :

f(x) = x² + 2x for x ≤ -3

That means for those values of x, less than or equal to -3, this is the function.

So, f(-3) = (-3)² + 2(-3) = 9 - 6 = 3

Now, f(-1) :

From the given data, we see it is: f(x) = 2
((1)/(3) )^(2x)

We take this because -1 lies between -3 and 4.

Now, f(-1) = 2
((1)/(3) )^(2(-1))

=>
f = (-1) = 2(3)^(2) = 2 (9) = 18

For f(4) :

Clearly, the function is:
f (x) = (2x - 5)/(x-7)


f (4) = (2(4)-5)/(4-7) = (3)/(-3) = -1

Therefore, f(-3) + f(-1) - f(4) = 3 + 18 - (-1) = 3 + 18 + 1 = 22.

User Mmacvicar
by
5.3k points